2018
DOI: 10.22159/ijpps.2018v10i1.21882
|View full text |Cite
|
Sign up to set email alerts
|

The N-Hexane Fraction of Myrmecodia Pendans Inhibits Cell Survival and Proliferation in Colon Cancer Cell Line

Abstract: Objective: Despite advanced treatment options available for colorectal cancer, many reported resistance and unresponsiveness to conventional chemotherapeutic agents. Therefore, it is urgent to discover a novel drug for colon cancer. Sarang Semut (Myrmecodia pendans), an Indonesian native plant, has been studied extensively due to its anti-cancer profiles. This study aimed to evaluate the anti-tumour activity of Sarang Semut in colon cancer cells. Methods:We evaluated cytotoxic activity of methanol extract as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…This grounded M. pendens was later macerated with methanol for 2-3 days followed by filtered then evaporated and dried into dry powder. This methanol extract was partitioned using n-hexane or ethyl acetate to yield n-hexane fraction or ethyl acetate fraction (Bashari, et al, 2018).…”
Section: Preparation Of Extract and Fractions Of Myrmecodia Pendensmentioning
confidence: 99%
See 2 more Smart Citations
“…This grounded M. pendens was later macerated with methanol for 2-3 days followed by filtered then evaporated and dried into dry powder. This methanol extract was partitioned using n-hexane or ethyl acetate to yield n-hexane fraction or ethyl acetate fraction (Bashari, et al, 2018).…”
Section: Preparation Of Extract and Fractions Of Myrmecodia Pendensmentioning
confidence: 99%
“…In particular cancer research, Sarang Semut plant has been shown cytotoxic effects in different cancer cell lines from different type of extractions (Soeksmanto, et al, 2010;Fatmawati, Puspitasari & Yusuf, 2011;Rifayani, et al, 2015;Bashari, et al, 2018). Sarang Semut extract has been shown to have a cytotoxic effect in HeLa and MCM-B2 cells (Soeksmanto, et al, 2010;Fatmawati, Puspitasari & Yusuf, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some mechanisms of action of flavonoids have been identified, such as inactivation of carcinogens, antiproliferation, cell cycle inhibition, apoptotic induction, inhibition of angiogenesis, antioxidants, or the combination of such mechanisms [33].…”
Section: Jainab and Rajamentioning
confidence: 99%
“…It is used empirically as a medical plant to treat various diseases. [11][12][13] This plant is valuable as an alternative endodontic irrigant and shows minimal side effects. Soraya (2016) found that M. pendens extract has an antibacterial effect against E. faecalis.…”
Section: Introductionmentioning
confidence: 99%